Effect of “Helping Babies Breathe” Training on Ethiopian Undergraduate Midwifery Students’ Knowledge and Skills in Neonatal Resuscitation at Public Universities: A Non-Randomized Quasi-Experimental Study - Endalew Gemechu Sendo; Girum Sebsibe Teshome; Wegnesh Kelbessa Jirata; Lemi Abebe Gebrewold; Rahel Endalew Gemechu (SAGE Open)
Helping Babies Breathe (HBB) is a global initiative launched by the American Academy of Pediatrics (AAP) in 2010, aimed at reducing neonatal mortality by addressing birth asphyxia, a leading cause of newborn deaths worldwide. The HBB training program trains providers in effectively resuscitating infants in developing countries, including Ethiopia. This study aims to examine the effects of HBB training on the knowledge and performance of undergraduate fourth-year midwifery students in neonatal resuscitation in public Ethiopian higher education institutions. The current study used a quasi-experimental study design. The study made use of the same research participants before and after the HBB Training. Pre- and post-knowledge tests, Objective structured clinical examinations (OSCEs), and a checklist for bag and mask ventilation skills checklist were used to assess the effectiveness of the HBB training. The data generated from pre and post-test results were imported into EPi Data version 4.0.2.49 and exported into SPSS version 25 for analysis. The data was correlated in nature due to its inherent source. After testing the assumptions, a paired t -test was used to examine the effect of HBB simulation training on the knowledge level of fourth-year midwifery students. The difference in the pre and post-training knowledge level of the students was declared as statistically significant at a p -value of .05. A total of 60 research participants from two public health science colleges that offer undergraduate midwifery training enrolled in this study; 54 of them received 2 days of HBB training in two phases and completed the pre- and immediate post-test course assessments. Six participants left the study for personal reasons. Of the participants in the study, 43 were female and 11 were male. The study participants were between the ages of 21 and 25, with a mean age of 22.47 years. The results demonstrated that, although before the intervention, over 25% of research participants (18; 29.63%) lacked adequate knowledge about managing birth asphyxia, all of them acquired adequate knowledge[≥80%] after the intervention. T -tests after the HBB intervention also revealed a substantial improvement in knowledge [ d ¯ + SE: 2.09 + 2.13, p < .001]. Similarly, following the HBB intervention, 43 research participants [or more than 3/4 of the sample] demonstrated appropriate skills [≥80%] for neonatal resuscitation, according to the findings of the OSCE-A and OSCE-B psychomotor skill assessments. The HBB program is a lifesaving training program designed for low-income countries. The study’s findings showed that the participants’ knowledge and skills of infant resuscitation were significantly improved by the HBB training course. The HBB training program has the utmost impact if pre-service refresher courses on neonatal resuscitation are offered to the midwife trainees before they join the national midwifery task forces.